2019
DOI: 10.1155/2019/3704198
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and Synergistic Antimicrobial Evaluation of Lipopeptides from Bacillus amyloliquefaciens Isolated from Oil-Contaminated Soil

Abstract: Lipopeptides show great potential for biomedical application. Several lipopeptides exhibit narrow and broad-spectrum inhibition activities. The aim of the study is to characterize the lipopeptides produced by B. amyloliquefaciens strain MD4-12 and evaluate the synergistic antimicrobial activity in combination with a conventional antibiotic against Gram-negative bacteria. B. amyloliquefaciens strain MD4-12 was isolated from oil-contaminated soil. The isolate was cultivated in McKeen medium, and the lipopeptides… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 39 publications
0
13
1
Order By: Relevance
“…The MIC was determined by resazurin assay in a 96 well-plate for P. aeruginosa (MIC 1024 g m ). The different surfactin isoforms could be a reason for the higher MIC compare to this work since Sudarmono et al [44] reported the presence of several isoforms of surfactin ( ), mainly surfactin and .…”
Section: Resultsmentioning
confidence: 46%
See 2 more Smart Citations
“…The MIC was determined by resazurin assay in a 96 well-plate for P. aeruginosa (MIC 1024 g m ). The different surfactin isoforms could be a reason for the higher MIC compare to this work since Sudarmono et al [44] reported the presence of several isoforms of surfactin ( ), mainly surfactin and .…”
Section: Resultsmentioning
confidence: 46%
“…Sudarmono et al [44] reported that surfactin produced by B. amyloliquefaciens presented antimicrobial activity against S. aureus ATCC 25923, P. aeruginosa ATCC 27853 and E. coli ATCC 25922, showing Inhibition zone diameter of 20.0, 15.7 and 11.4 mm, respectively. The MIC was determined by resazurin assay in a 96 well-plate for P. aeruginosa (MIC 1024 g m ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Surfactins are cyclic lipopeptides with surfactant-like properties, interfering with many kinds of cell membranes. They were reported to show antibacterial activity in agar diffusion assays against various test strains if used at high concentrations 55,56 . However, these results must be interpreted with caution, since the MICs determined were > 1024 µg/mL 56 , indicating no activity.…”
Section: Discussionmentioning
confidence: 99%
“…They were reported to show antibacterial activity in agar diffusion assays against various test strains if used at high concentrations 55,56 . However, these results must be interpreted with caution, since the MICs determined were > 1024 µg/mL 56 , indicating no activity. The debate on the antimicrobial effect of surfactins remains active, but may be accounted to the non-specific mode of action on the cell layer, e.g.…”
Section: Discussionmentioning
confidence: 99%